2017
DOI: 10.1007/978-3-319-62274-3_11
|View full text |Cite
|
Sign up to set email alerts
|

Rotating Machine Prognostics Using System-Level Models

Abstract: The prognostics of rotating machines is crucial for the reliable and safe operation as well as maximizing usage time. Many reliability studies focus on component-level prognostics. However, in many cases, the desired information is the residual life of the system, rather than the lifetimes of its constituent components. This review paper focuses on system-level prognostic techniques that can be applied to rotating machinery. These approaches use multi-dimensional condition monitoring data collected from differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…While there have been similar papers that have reviewed algorithms for the systemlevel prognostics [32], this section summarizes them once again very briefly for the purpose of integrity as they appear in the subsequent sections. It is again emphasized that the algorithms reviewed herein are not limited to the system.…”
Section: Algorithms For System-level Prognosticsmentioning
confidence: 99%
See 2 more Smart Citations
“…While there have been similar papers that have reviewed algorithms for the systemlevel prognostics [32], this section summarizes them once again very briefly for the purpose of integrity as they appear in the subsequent sections. It is again emphasized that the algorithms reviewed herein are not limited to the system.…”
Section: Algorithms For System-level Prognosticsmentioning
confidence: 99%
“…All these are the issues around the system-level prognostics. Despite its importance and challenges, only a few reviews are found on the systemlevel prognostics [30,32]. Li et al [32] summarized prognostics algorithms for rotating machinery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such analyses were traditionally based on a single parameter, but an Industry 4.0 environment combines several different sensor signals and parameters (i.e., process, health and performance indicators) with enterprise-level data (e.g., production forecasts, spare part management, and equipment information), all the way down to the component level [2]. These novel techniques for data acquisition and analysis require new algorithms that manage the analysis of multivariate sensor signals (i.e., big data) to perform accurate and reliable detection, diagnosis, and prognosis of the equipment or component of interest [3]. The use of predictive maintenance (PdM) in Industry 4.0 is expected to yield many benefits [4], but the extent of the enhancements (i.e., levels of detection, diagnosis, and prognosis) is not yet known.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, such analyses were based on a single parameter originating from one sensor; in contrast, the Industry 4.0 environment requires combining several different sensor signals and parameters, ie, process and health, with enterprise level data 28 . Furthermore, the new techniques for data acquisition and analysis require new algorithms that analyze the big data from these multivariate sensor signals to perform accurate and reliable diagnosis and prognosis 29 . This calls for a PdM architecture that integrates enterprise‐level data with monitoring data, ie, performance and health parameters 14 …”
Section: Introductionmentioning
confidence: 99%